GASTRONOMIK TURIZMNING MADANIY VA IQTISODIY RIVOJLANISHDAGI O’RNI - Sunnatova Sevara (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Gastronomic tourism, also known as culinary tourism, is a rapidly growing sector within the global tourism industry. It involves tourists engaging with local culinary traditions, contributing to cultural exchange and economic growth. This article explores the definition of gastronomic tourism, its significance in enhancing local identity, and its economic potential. Case studies from major culinary destinations such as Bangkok, Istanbul, and Tokyo illustrate how gastronomic tourism fosters cultural understanding and boosts the local economy by attracting international visitors.